2010
DOI: 10.1111/j.1365-2842.2010.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

Designing cobalt chromium removable partial dentures for patients with shortened dental arches - a pilot survey

Abstract: The aim of this survey was to investigate the quality of prescription for the fabrication of cobalt chromium removable partial dentures (RPDs) that are used to extend the shortened dental arches (SDAs). A survey of four commercial dental laboratories located in northern England was conducted. The target of this survey was cobalt chromium RPDs that were requested to restore SDAs comprising the anterior teeth and 2-4 premolars. Dentists' prescriptions were scrutinised, and a special data collection form was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Table 3 illustrates that when instructions were provided, the shape of the major connector was the most frequent element to be prescribed by the surveyed dentists (35.8%). This is similar to the outcome of a UK survey where the design of the major connector was the most common component in dentists' prescriptions (59%) (30). The reason why dentists in this survey give more attention to the design of the major connector in comparison with the other elements of the cobalt chromium RPDs is not clear.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Table 3 illustrates that when instructions were provided, the shape of the major connector was the most frequent element to be prescribed by the surveyed dentists (35.8%). This is similar to the outcome of a UK survey where the design of the major connector was the most common component in dentists' prescriptions (59%) (30). The reason why dentists in this survey give more attention to the design of the major connector in comparison with the other elements of the cobalt chromium RPDs is not clear.…”
Section: Discussionsupporting
confidence: 80%
“…During each visit dentists' prescriptions were scrutinized, targeted casts were examined and a special data collection form was completed. The data collection form was a modified version of the one that was used in a previous investigation (30). Before the outset of the survey, the developed form was also distributed among 6 dental technicians to provide feedback about the clarity and feasibility of the contents.…”
Section: Methodsmentioning
confidence: 99%
“…These guidelines were based on the best available evidence for what can be considered a good clinical practice in prosthodontics. They also guide clinicians to make the best clinical judgment and pave their way to deliver prosthodontic treatment of high standards; however, studies that assessed quality of clinical procedures and standards of technical work in prosthodontics indicated unsatisfactory findings among a considerable proportion of the examined cases . Furthermore, a large number of studies reported failure of prosthetic dental restorations and associated complications .…”
Section: Standards Of Care and Malpractice In Prosthodontics—an Overvmentioning
confidence: 99%
“…On the other hand, poor communication between the dentist and dental technician is a mark of malpractice. Unfortunately, the dental literature indicates inappropriate quality of communication between dentists and dental technicians in designing fixed and removable dental prostheses . The introduction of digital dentistry has provided modern ways for fabrication of prosthetic dental restorations and communicating prosthesis design between dentists and technicians.…”
Section: Malpractice In Prosthodontics—where and How Does It Occur?mentioning
confidence: 99%
“…Furthermore, inadequate quality of prescription in designing RPDs for patients with SDAs has been reported. [30]…”
Section: Clinical Investigations On the Outcome Of Treatment With Fesmentioning
confidence: 99%